PENGARUH LUMPUR SAWIT TERHADAP DAYA SIMPAN DAN PALATABILITAS PAKAN PELLET KELINCI - Amir Husaini Karim Amrullah; Fregi Fehriansah; Irma Badarina (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2021)
ABSTRACT The study aims to evaluate the use of palm decanter on storability and palatability of pellet rabbit feed. There were four treatments, P0: rabbit pellets 0% palm decanter, P1: rabbit pellets 5% palm decanter, P2: rabbit pellets 10% palm decanter, P3: rabbit pellets 15% palm decanter. Pellets are prepared based on the standard nutritional needs of rabbits. Pellets were stored in 0.5 kg plastic bags for 0, 7, 14, and 21 days. Moisture, crude fat, and organoleptic content were carried out on pellet with storage times 0, 7, 14, and 21 days. Organoleptic was carried out by 20 panelists. Palatability was carried out for a pellet with seven days of storage and given to 5 rabbits. The moisture and crude fat content of pellet in all treatments ranged from 8.63-10.17%. The higher the palm decanter content, the pellet color tends to be black with a value of 2.6-4.3. The use of 15% palm decanter can cause pellets to have a slightly rancid aroma and a characteristic solid odor. The use of 15% palm decanter did not have a significant effect on rabbit feed consumption with the consumption range 74.93-145.73 g. The study concluded that rabbit pellets containing up to 15% palm mud with a storage time of 21 days did not reduce storability. Pellets containing up to 15% palm mud with a storage time of 7 days did not reduce palatability in rabbits. Key Words: palm decanter, pellet, rancidity, feed, palatability